Indonesian Omnichannel Banking: How Far Do Governing Laws Protect Customer's Data Privacy - Fontian Munzil; Nadisah Zakaria (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
In the digital transformation era, banks have been working to implement a digital strategy that will lead to lower costs, better service, higher profitability, and the desired level of customer satisfaction. Utilising marketing technology for consumer engagement is essential to bringing in more customers without increasing costs. Omnichannel is the marketing strategy that offers more services to customers by having them interact with it across all available physical and digital channels at any time, resulting in higher customer satisfaction and loyalty. Customer data is significant information that may be used at any stage of the digital marketing process. The Protection of Personal Data Act of 2022 and the Act of Development and Strengthening of the Financial Sector of 2023 govern consumer data protection at all stages of marketing activities, including data processing, profiling, and collaboration with other organisations. This study reviews how far the governing laws can protect consumer private data in utilisation in the company's digital marketing program to boost utilisation of the company's omnichannel approach. The study discovered that governing laws can protect the customer's private data in the banking omnichannel approach. Customer data are governed clearly and strongly by the regulations at all marketing program phases that could potentially be exploited, so both laws will be able to prevent illegal activities of customer data optimally in the future. Lastly, customer approval is critical for the Bank's use of all customer data.